The Role of the Tuah Negeri Nusantara Legal Aid Institute in Law Enforcement - Samariadi,; Br Panjaitan, Andra Wina; Safitri, Fira; Yulisa, Farah Amalia; Permatasari, Mutiara; Rahman, Azra Aulia; Jaizna, Muhammad Nabiel; Novriano, Rama (Jurnal Pengabdian Masyarakat, 2024)
Purpose: This paper examines the role of the Tuah Negeri Nusantara Legal Aid Institute in Riau, Indonesia, highlighting its professional legal assistance, education, and reform efforts. It explores the significance of legal aid in addressing the region's growing need for accessible legal support. Method: A qualitative review of the institute’s activities, including case records and interviews with legal professionals, was conducted. The study focuses on the institute’s handling of over 500 cases since 2016 and its broader contributions to legal reform. Practical Applications: The findings demonstrate the institute’s vital role in providing legal aid to underserved communities and its influence on legal education and reform. These contributions offer a model for improving access to justice in other regions. Conclusion: The Tuah Negeri Nusantara Legal Aid Institute has had a substantial impact on the legal sector in Riau, handling over 500 cases since 2016. Its work highlights the importance of legal aid in promoting justice and advancing legal knowledge in Indonesia.